Uso de planilhas eletrônicas do Excel (ou Libre Office) como ferramentas de ensino de matemática em sala de aula - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study presents the applicability of electronic spreadsheets to the teaching of financial mathematics, statistics, and first- and second-degree functions through both theoretical and practical use of Microsoft Excel. The research was initially conducted from a theoretical perspective, demonstrating the procedures for solving mathematical problems with the aid of Excel. Furthermore, a workshop was implemented at an Indigenous school located in the rural area of Santarém, with a primary focus on the use of LibreOffice Calc software to solve problems related to financial mathematics, statistics, and functions. The methodology adopted included a literature review, the design and implementation of a workshop with students, and the use of assessment forms administered before and after the activities. The results obtained indicate that the use of spreadsheets significantly contributed to students' understanding of the content, as well as fostering interest and active participation. It is concluded that the integration of technological tools constitutes an effective and accessible alternative for diverse educational contexts, provided that they are applied with pedagogical intent and focused on the comprehension of mathematical concepts.
Keywords: Planilhas Eletrônicas; Matemática Financeira; Estatística; Funções Polinomiais; Excel; Educação; CNPQ::CIÊNCIAS HUMANAS